Antitumor effect of the Newcastle disease virus strain NDV/Altai/pigeon/777/2010 on a model of solid Lewis carcinoma - Yu. I. Karkavin; L. S. Adamenko; K. S. Yurchenko; A. V. Glushchenko (Юг России: экология, развитие)
Aim. To evaluate the efficacy of intratumoral administrations of the Newcastle disease virus strain NDV/Altai/pigeon/777/2010, to compare progression of the tumor nodes after virotherapy and to analyse pathomorphological changes in the tumor tissue in vitro and in vivo. Single intratumoral injections of the mesogenic strain of Newcastle disease virus NDV/Altai/pigeon/777/2010, isolated from a rock dove in Siberia, were done into outbred mice of the C57Bl/6 line into solid nodes of Lewis lung carcinoma that were grafted subcutaneously. Then the dynamics of tumor growth and pathomorphological changes in the tumor tissue were assessed and analyzed.It was shown that single intratumoral injections into immunocompetent C57Bl/6 mice with the mesogenic strain of Newcastle disease virus NDV/Altai/pigeon/777/2010 led to an increase in peculiar pathomorphological changes in the tumor tissue of subcutaneously grafted Lewis lung carcinoma and to a decrease in tumor growth compared to the control group of mice in vivo. A direct cytotoxic effect of the NDV strain on the Vero E6 cell line in vitro was noted.The results of this study indicate that the NDV strain NDV/Altai/pigeon/777/2010 has antitumor properties. This may enable clinical trials to prove its effectiveness as an antitumor drug.